1989
DOI: 10.1139/x89-136
|View full text |Cite
|
Sign up to set email alerts
|

Trends in genetic and environmental parameters, genetic correlations, and response to indirect selection for 10-year volume in a Norway spruce clonal experiment

Abstract: Seventy-five clones of Norway spruce (Piceaabies (L.) Karst.) were tested for height, diameter, and volume at two locations in southern Sweden. Total height was measured at seven ages from age 1 to 10 years, whereas diameter at breast height was measured and volume index calculated only at age 10. Clone effects were consistently significant for all traits, whereas clone × location interaction effects only showed significance for diameter at breast height at age 10, volume index, and height at age 3. Location e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Estimates of h 2 for tree height were lower (0.04-0.07) than the values of other published results with seedlings using joint-site models for Norway spruce (Chen et al 2015(Chen et al , 2017Skrøppa et al 2015). Estimates of H 2 for tree height were in the range 0.12-0.16 which is comparable with other studies, such as 0.13 for tree height at age 6 (excluding G × E) (Karlsson and Högberg 1998), 0.17-0.29 for tree height at age 9 (including G × E) (Högberg and Karlsson 1998), 0.25-0.29 for tree height at ages 3 to 10 years (Bentzer et al 1989), and 0.09-0.43 for tree height at ages 9 to 18 years (including G × E) (Högberg and Dutkowski 2010), and 0.10-0.22 for height at age 17 (including G × E). Compared with those published studies with high prior intense selection in the nursery, the difference here may be that only a slight prior selection was performed and that may produce less bias in the estimation of h 2 and H 2 .…”
Section: Heritability Of Growth Traitssupporting
confidence: 87%
See 1 more Smart Citation
“…Estimates of h 2 for tree height were lower (0.04-0.07) than the values of other published results with seedlings using joint-site models for Norway spruce (Chen et al 2015(Chen et al , 2017Skrøppa et al 2015). Estimates of H 2 for tree height were in the range 0.12-0.16 which is comparable with other studies, such as 0.13 for tree height at age 6 (excluding G × E) (Karlsson and Högberg 1998), 0.17-0.29 for tree height at age 9 (including G × E) (Högberg and Karlsson 1998), 0.25-0.29 for tree height at ages 3 to 10 years (Bentzer et al 1989), and 0.09-0.43 for tree height at ages 9 to 18 years (including G × E) (Högberg and Dutkowski 2010), and 0.10-0.22 for height at age 17 (including G × E). Compared with those published studies with high prior intense selection in the nursery, the difference here may be that only a slight prior selection was performed and that may produce less bias in the estimation of h 2 and H 2 .…”
Section: Heritability Of Growth Traitssupporting
confidence: 87%
“…The Swedish breeding program for Norway spruce has been focused on growth, survival, branch quality, and wood density (Rosvall et al 2011). Genetic parameters have been estimated for many full-sib and half-sib seedling progeny trials (Hannrup et al 2004;Kroon et al 2011;Chen et al 2014) and also for clonal trials, but without family structure (Bentzer et al 1989;Karlsson et al 2001;Högberg and Dutkowski 2010;Isik et al 2010). A most recent study of Norway spruce in clonal trials included family structure (Berlin et al 2019), but considered just growth properties.…”
Section: Introductionmentioning
confidence: 99%
“…In clonal tests of balsam fir (Picea abies [L.] Karst) produced from rooted cuttings, Isik et al (2010) also observed that height at 5 yr was highly correlated with that at 3 yr (r G = 0.85). Genotypic correlations between height at 4 yr of age Norway spruce clones and heights at later ages all equaled or exceeded 0.95 (Benzer et al, 1989). These authors provided that the early selection for height at age 4 was good predictor of larger volume index at age 10.…”
Section: Age-age Genotypic Correlationmentioning
confidence: 84%
“…The H c 2 values in the nursery are similar to the clonal heritabilitie for the height of on1-yr-old Norway spruce (Picea abies [L.] Karst.) grown from cuttings (H c 2 = 0.40; Benzer et al, 1989). On both two planting sites, the clonal heritabilities for height-calculated at 1, 2, 3, and 4 yr after outplanting in the present study-are lower than the individual heritabilities (h 2 = 0.40 to 0.65) of 9-yr-old plantation-grown white spruce in different regions of Ontario (Lake Tomahawk, Wabeno, Moran; Nienstaedt & Riemenschneider, 1985).…”
Section: Downloaded By [University Of Montana] At 17:07 01 April 2015mentioning
confidence: 99%
See 1 more Smart Citation